EXPLORING THE INFLUENCE OF ARTIFICAL INTELLIGENCE ON THE BUSINESS LANDSCAPE IN INDIA: AN IN-DEPTH ANALYSIS AND IMPLEMENTATION IN BANKING SECTORS: EXPLORING THE INFLUENCE OF ARTIFICAL INTELLIGENCE ON THE BUSINESS LANDSCAPE - Reddy, Anupama; Padmalatha (The journal of contemporary issues in business and government, 2024)
The proposed research work explores the Influence of AI on the business landscape in India with an in-depth analysis & its implementation in few sectors. This research delves into the transformative impact of Artificial Intelligence (AI) on the business landscape in India, conducting a comprehensive and in-depth analysis. The study aims to unravel the multifaceted ways in which AI technologies are shaping the strategies, operations, and competitiveness of businesses across various sectors in the Indian economy. Through a combination of empirical research, case studies, and industry interviews, the research seeks to identify key trends, challenges, and opportunities arising from the integration of AI into business practices. The investigation spans diverse domains, including finance, healthcare, manufacturing, and services, aiming to capture the nuanced effects of these technologies on productivity, innovation, and overall business performance. Furthermore, the study explores the readiness of Indian businesses to adopt and implement AI solutions, examining the factors influencing successful integration and potential barriers hindering widespread adoption. As an integral part of the research, the study also emphasizes the practical aspects of implementation, providing insights into best practices and strategies for businesses aiming to leverage AI technologies effectively. By doing so, it contributes actionable recommendations to industry stakeholders, policymakers, and academia, fostering a more informed and strategic approach to navigating the evolving landscape of business in the era of AI. Ultimately, this research aspires to be a valuable resource for decision-makers, offering a holistic understanding of the current state and future trajectory of AI in the Indian business ecosystem. This research further investigates the impact of Artificial Intelligence (AI) on the service sector, a pivotal contributor to a country's socio-economic growth. With a focus on gathering primary data from AI-utilizing organizations and secondary information from researchers, the study aims to analyze and draw conclusions regarding the effects of AI on both productivity and customer satisfaction. As consumer expectations for enhanced and faster services persist, companies are adapting by integrating AI, making it crucial to understand the implications of this technological shift. In the proposed work, a service sector in the country is taken into consideration. The service sector significantly contributes to a country's socio-economic growth, driven by an increasing demand for better and faster services from consumers. To meet this demand, companies are continually innovating, and a notable shift in this sector involves the adoption of Artificial Intelligent Chatbots. These chatbots offer rapid responses at a minimal cost compared to human support, transforming customer interactions. While AI continues to evolve and is considered young by scientists, it has already proven efficient in replacing repetitive mundane tasks. This study aims to collect primary data from organizations utilizing AI chatbots and secondary information from researchers, with the goal of analyzing and concluding the impact of AI Chatbots on both productivity and customer satisfaction. To begin with, first a survey was conducted amongst 5 Asian countries (one amongst them being India) and the analysis was carried out, the results discussed and summarized. The future works plans to develop more business canvas models for the successful implementation of AI not only in banking sector, but also in a large no. of establishments.